Time in range, assessed with continuous glucose monitoring, is associated with brachial-ankle pulse wave velocity in type 2 diabetes: A retrospective single-center analysis - Zhou, Hui; Wang, Wei; Shen, Qiuyue; Feng, Zhouqin; Zhang, Zhen; Lei, Haiyan; Yang, Xinyi; Liu, Jun; Lu, Bin; Shao, Jiaqing; Gu, Ping (Frontiers in Endocrinology, 2022)
Aims： The aim of this study is to research the relationship between time in range(TIR), an important novel metric of glycemic control, assessed with continuous glucose monitoring(CGM) and brachial-ankle pulse wave velocity(BaPWV)，a unique index of systemic arterial stiffness in type 2 diabetes. Methods: Study participants included 469 hospitalized patients with type 2 diabetes and no history of serious cardiovascular disease who underwent CGM and BaPWV measurements. TIR of 3.9-10.0 mmol/L was evaluated with CGM. BaPWV was measured by non-invasive arteriosclerosis detector and high baPWV was defined as a mean baPWV≧1800m/s. The spearman correlation and the partial correlation analysis were applied to analyze the correlation betweeen TIR and baPWV. The binary logistic regression was used to examine the independent association of TIR and high BaPWV. Results: The presense of high baPWV was 32.2%. Compared with patients of low baPWV, those with high baPWV had significantly reduced TIR(P<0.001). With the increase of TIR tertiles, the precalence of high BaPWV progressively decreased. Correlation analysis showed that TIR is inversely correlated with BaPWV. In a fully adjusted model controlling for traditional risk factor of CVD, TIR is associated with the presence of high BaPWV independent of HbA1c. Conclusion: TIR is correlated with BaPWV independent of HbA1c in patients with type 2 diabetes, confirming a link between TIR and arterial stiffness.